2012
DOI: 10.1038/ncomms2130
|View full text |Cite
|
Sign up to set email alerts
|

Probing the tunnelling site of electrons in strong field enhanced ionization of molecules

Abstract: molecules show a much increased multiple ionization rate in a strong laser field as compared with atoms of similar ionization energy. A widely accepted model attributes this to the action of the joint fields of the adjacent ionic core and the laser on its neighbour inside the same molecule. The underlying physical picture for the enhanced ionization is that it is the up-field atom that gets ionized. However, this is still debated and remains unproven. Here we report an experimental verification of this long-st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
91
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 32 publications
8
91
1
1
Order By: Relevance
“…We use the rotating electric-field vector of the laser pulse as ultrafast clockwork and measure the asymptotic emission direction f el of the tunnelionized electron. The value of f el between 0 and 2p provides the laser phase, relative to an arbitrary reference axis in the laboratory frame, at the ionization instant t i [10][11][12][13][14][15] . However, it is not f el, but rather f el mol , the phase of the laser field relative to the molecular axis at time t i , which determines the degree of anisotropy in bond breaking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We use the rotating electric-field vector of the laser pulse as ultrafast clockwork and measure the asymptotic emission direction f el of the tunnelionized electron. The value of f el between 0 and 2p provides the laser phase, relative to an arbitrary reference axis in the laboratory frame, at the ionization instant t i [10][11][12][13][14][15] . However, it is not f el, but rather f el mol , the phase of the laser field relative to the molecular axis at time t i , which determines the degree of anisotropy in bond breaking.…”
Section: Resultsmentioning
confidence: 99%
“…The first technique combines a single attosecond pulse with an intense near-infrared laser pulse, such that the attosecond pulse acts as a start and the phase-locked infrared pulse streaks a freed electron in energy [6][7][8][9] . The second technique, termed 'attosecond angular streaking', uses elliptically polarized light [10][11][12][13][14][15] and adopts either the major axis of the elliptical field or the carrier-envelope phase (CEP) of a CEP-stabilized pulse to provide a reference time. A released electron is then driven to a certain direction by the rotating electric field, which maps the ionization instant within one laser cycle (T p B2.6 fs at 790 nm) to the 2p interval of electron emission directions (B7.3 attosecond for 1°) in the polarization plane.…”
mentioning
confidence: 99%
“…The observed forwardbackward dissociation asymmetries imply that the electron is preferentially emitted from the down-field site, in contradiction with the DIU physical picture. Recently, a single-color elliptically polarized laser pulse is used to probe the tunnelling site of electrons from the dimer ArXe by angular streaking technique [23,24]. Wu et al reported that the ionization more easily happens at the up-field site, supporting the DIU physical picture.…”
mentioning
confidence: 82%
“…Wu et al reported that the ionization more easily happens at the up-field site, supporting the DIU physical picture. Because the intuitive physical picture is based on the quasi-static theory, lacking a perspective on the dynamics of ionization processes, controversy still exists in these experiments.To understand the long-standing issues about EI [22,23,[25][26][27], in this Letter, we investigate the electron dynamics and the tunnelling site by carefully examining time evolution of the electron density and ionization rate with numerically solving time-dependent Schrödinger equation (TDSE). A more comprehensive physical picture is established for EI dynamics of diatomic molecules.…”
mentioning
confidence: 99%
“…Our work clarifies the long-standing controversy and strengthens the theoretical basis of molecular orbital tomography. The fast development of strong-field physics has provided versatile perspectives for probing the structure and ultrafast electron dynamics in atoms and molecules with attosecond andÅngstörm resolutions [1][2][3][4][5]. A fascinating application, known as molecular orbital tomography (MOT) based on high-order harmonic generation (HHG), has attracted a great deal of attention for its potential use of observing chemical reactions in molecules by directly imaging the valence molecular orbital [6][7][8][9][10][11][12][13][14].…”
mentioning
confidence: 99%